Implementation of the “Babonisasi” system of environmentally friendly kampong chicken based on household waste for increasing income of KWT Banyusidi Village - Setyo Utomo; Nur Rasminati; Ajat Sudrajat (Community Empowerment, 2023)
The purpose of this activity is to apply the "Babonisasi" system for kampong chicken to empower the community's economy, especially for hopeful families. This program was held in collaboration with UPSI Malaysia and UMBY through knowledge transfer using a zoom meeting attended by Bappeda Magelang Regency with participants from all members of KWT Larasati, young people, and UPSI Malaysia students. Transfer of knowledge includes the implementation of the babonisasi system for groups, the correct implementation of free-range chicken maintenance and care, kampong chicken IB, economic analysis calculations for kampong chicken business, disease prevention and vaccination efforts and utilization of household waste as animal feed. It was concluded that all of the existing members (20 people) had carried out routine maintenance in group cages and had understood vaccination and feeding techniques (30%).